2020
DOI: 10.1111/tbj.13975
|View full text |Cite
|
Sign up to set email alerts
|

Is radial scar on core needle biopsy a risk factor for malignancy? A single‐center retrospective review and implications for management

Abstract: Introduction Reported upgrade rate to malignancy of radial scars (RS) ranges widely (0%‐40%) making management controversial. Methods A retrospective chart review was performed on patients with RS on core needle biopsy (CNB). Upgrade rates to malignancy and atypia on surgical excision were evaluated. Results Of 127 patients with RS on CNB, 53 were excluded due to malignancy or missing records. Of 74 patients reviewed, 52 (70.3%) had surgical excision with four (7.7%) upgraded to malignancy. Eight patients (10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In Woodward et al, 7 a retrospective review using a single institutional pathology and radiology database was conducted for all radial scars identified on core biopsy from January 2010 to January 2017. The mean age of the patients with benign biopsies was 52.9 years old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Woodward et al, 7 a retrospective review using a single institutional pathology and radiology database was conducted for all radial scars identified on core biopsy from January 2010 to January 2017. The mean age of the patients with benign biopsies was 52.9 years old.…”
Section: Resultsmentioning
confidence: 99%
“…The overall underestimation rate was 38% and the invasive lesion underestimation rate was 2.2%. 7 Gašljević et al, 8 in a retrospective study using a database from the Slovenian National Breast Cancer Screening Program, checked all patients with a radial scar or a complex sclerosing lesion who underwent core needle biopsy between 2008 and 2018. The mean age was 61.5 years old.…”
Section: Resultsmentioning
confidence: 99%
“…As the histology of these lesions is similar to breast carcinoma, some studies have identified RS as an independent risk factor for developing breast cancer. 5,6 However, other studies do not support a strong relationship, leading to uncertainty with management of these lesions. 7 It has been shown that stereotactic CNB can underestimate presence of in situ or invasive disease on final excisional biopsy.…”
Section: Discussionmentioning
confidence: 99%